The influence of electronic health record design on usability and medication safety: systematic review - Marie Cahill; Brian J. Cleary; Shane Cullinan (BMC Health Services Research)
Abstract Background The advantages of electronic health records (EHRs) are well-documented regarding the process of care, enhanced data accessibility and cost savings. However, EHR design can also contribute to usability challenges, with poorly designed EHRs being implicated in user errors including patient overdoses. Our study seeks to evaluate how EHR design influences both usability and medication safety. Methods A systematic review was conducted of PubMed, EMBASE, CINAHL and the ACM library from 1 January 2009 to 8 October 2024. Eligible studies reported on the impact of specific EHR design elements on usability and/or medication safety, involved healthcare providers and took place in a secondary, tertiary or quaternary care setting. Usability was defined as the extent to which an EHR can be used to achieve specified goals with effectiveness, efficiency and satisfaction, while medication safety related to the risk of drug-related problems, including adverse drug events and medication errors. Design features identified within studies were validated, by cross-referencing these elements with ISO standards regarding design recommendations. A narrative synthesis was conducted, with studies tabulated based on whether they assessed usability and/or medication safety. Patterns were identified and common design elements between studies translated into themes. The Mixed Methods Appraisal Tool was used to evaluate study quality and PRISMA guidelines were followed throughout. Results Thirty-two studies were identified. The design features described in these studies fit within seven broad design themes: searchability, automation, customisation, data entry, workflow, user guidance and interoperability. EHR systems that prioritised these areas were associated with higher reported usability and enhanced medication safety, while the opposite was found for systems that overlooked these design aspects. Our review also highlighted the numerous ways these themes can be implemented, while identifying the contributing factors that enable their successful implementation. Conclusion The design of EHRs can enhance or undermine usability and medication safety, depending on the searchability and customisability of these systems, how data entry processes and provider workflow are facilitated and how automation, user guidance and interoperability are implemented. Future EHR evaluations should be performed throughout the design process and consensus building is required regarding what exactly constitutes a design element, within an EHR context.